A new critical methodology of cosmopoliticization - Klinke, Andreas (Frontiers in Political Science, 2024)
A critical methodology of cosmopoliticization describes a new theoretically guided approach of empirical analysis to capture phenomena and quality of cosmopoliticization. The study and interpretation of cosmopoliticization and cosmopolitanism needs a critical pivot that draws on empirical issues and social facts to some extent to advance the theorizing of notions of cosmopolitan governance and democracy. First, I substantiate the rationale behind a new critical methodology of cosmopoliticization. Then, I argue that the sources of real-world insights of cosmopolitan practices and experiences can be derived from empirical analyses of three major subject matters, namely the formation of cosmopolitan solidarity, ethos, and belief, the role of cosmopolitan public spheres, and international democratization through civil society participation and deliberation. These analytical categories and units can convey cosmopolitan values and principles that are critical of a significant cosmopolitan departure from dominant nation-state related paradigms and politics because they embody an impetus for recognition and esteem of the ecological and ethical value and meaningfulness of the entire earth system for humankind in terms of a right conduct and practice in present and future.